2018
DOI: 10.1017/s0892679418000291
|View full text |Cite
|
Sign up to set email alerts
|

Extractivism, Gender, and Disease: An Intersectional Approach to Inequalities

Abstract: Social inequalities can only be understood through the interaction of their multiple dimensions. In this essay, we show that the economic and environmental impacts of natural resource extraction exacerbate gendered disparities through the intensification and devaluation of care work. A chikungunya epidemic in the refinery city of Esmeraldas, Ecuador, serves to highlight the embodied and structural violence of unhealthy conditions. Despite its promises of development, the extraction-based economy in Esmeraldas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…The results of this study are consistent with those of previous studies that reported a high burden of VBD in South America, especially in areas with limited access to healthcare and poor living conditions [ 33 ]. Moreover, as exposure to vectors is an essential factor in relative gendered risks for contracting infectious diseases, and as gender-differentiated activities and spaces determine this exposure and given that susceptibility to VBD has social relations, especially under extractive contexts such as Ecuadorian one, policies must consider the gender, race, and class determinants of health [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study are consistent with those of previous studies that reported a high burden of VBD in South America, especially in areas with limited access to healthcare and poor living conditions [ 33 ]. Moreover, as exposure to vectors is an essential factor in relative gendered risks for contracting infectious diseases, and as gender-differentiated activities and spaces determine this exposure and given that susceptibility to VBD has social relations, especially under extractive contexts such as Ecuadorian one, policies must consider the gender, race, and class determinants of health [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…2. Cuando las lógicas de urbanización más remota llegan hasta los territorios indígenas, hay procesos de oposición y negociación a los diferentes proyectos que tienen una amplia literatura (Cielo y Coba, 2018). Nos centraremos aquí en aquellas negociaciones respecto al extractivismo donde las comunidades logran una inversión en forma de urbanización.…”
Section: Casos De Estudiounclassified
“…A similar argument is made by Landívar García [58] analysing the gendered structure of agrarian extractivism concerning sugarcane in Ecuador. Looking at the chikungunya epidemic in the refinery city of Esmeraldas in Ecuador, a recent study concludes: "Extractivism exacerbates the already heavy burden of women's care work, thus forming a central mechanism of the 'illness-poverty trap' by which ill health is both a consequence of and a contributor to inequalities" [59] (p. 169).…”
Section: Actors and Power Relations In The Soy Complex And The Bioeco...mentioning
confidence: 99%